Typical investigative situations as prerequisites for formation of interrogation algorithms - Sokolenko, Mykyta (Archives of Criminology and Forensic Sciences, 2024)
Article Purpose is to analyze investigative situations as prereq-uisites for the construction and implementation of interrogation al-gorithms, to consider approaches to their typification, identify typical interrogation situations that form the basis for formation of interroga-tion algorithms. Investigation of crimes includes planning, organizing and conduct-ing a certain set of investigative actions and tactical operations, which successful implementation should lead to the achievement of the desired results: namely: estab-lishment of the truth in a criminal case. In this regard, the practice of investigating crimes defines a certain range of investigative actions, which allows us to assert some typification of the aggregate of the latter. In addition, despite the diversity of investigative situations, they can be combined into several most characteristic groups, that is, typified. This gives reason to believe that it is possible to apply an orderly and consistent execution of actions according to certain prescriptions that make up the algorithm.